Biomass-derived carbon decorated with Ni0.5Co0.5Fe2O4 particles towards excellent microwave absorption performance. (May 2022) - Sun, Jin; Chen, Juan; Ge, Heyi; Sun, Hao; Yang, Yuxuan; Zhang, Youzhong
Highlights: The microwave absorber of pomelo peel-derived carbon decorated with Ni0.5 Co0.5 Fe2 O4 was prepared. The minimum reflection loss reaches −41.6 dB and the effective absorption bandwidth is 4.3 GHz. The skeleton structure improved the impedance matching, increased the attenuation of absorber by Debye relaxation, multiple reflections and scattering. Abstract: Searching for high efficiency microwave absorbers is to meet the requirements of elimination of electromagnetic pollution. Herein, the Ni0.5 Co0.5 Fe2 O4 decorated pomelo peel-carbon microwave absorber with uniform particle size was prepared by a facile physical blending method. The skeleton structure formed by biomass carbon (BC) can not only effectively improve the conductive loss, but also extend the propagation path of electromagnetic waves. Besides, the absorber with a great quantity defects and heterogeneous interfaces delivers interfacial polarization and dipole polarization. Also, the Ni0.5 Co0.5 Fe2 O4 particles with good dispersion on BC are beneficial toward dielectric-magnetic combination, resulting in impedance matching. The minimum reflection loss (RL) reaches −41.6 dB and the effective absorption bandwidth (EAB) (RL < −10 dB) is 4.3 GHz with the thickness of 3 mm. This work will promise a good approach to accomplish high performance of microwave absorption.